2017
DOI: 10.1002/2017jd026679
|View full text |Cite
|
Sign up to set email alerts
|

Toward quantitative forecasts of volcanic ash dispersal: Using satellite retrievals for optimal estimation of source terms

Abstract: Airborne volcanic ash is a hazard to aviation. There is an increasing demand for quantitative forecasts of ash properties such as ash mass load to allow airline operators to better manage the risks of flying through airspace likely to be contaminated by ash. In this paper we show how satellite‐derived mass load information at times prior to the issuance of the latest forecast can be used to estimate various model parameters that are not easily obtained by other means such as the distribution of mass of the ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 45 publications
6
33
0
Order By: Relevance
“…The ability to make use of ash polygons based on various sources of information about ash presence (including inputs from skilled forecasters) and demonstrated reliability make this method ideal for operational use. The sources considered in this paper have not been optimized to make quantitative forecasts of mass loadings, which are in increasing demand; this issue is addressed in another paper [ Zidikheri et al , ]. However, while volcanic ash advisories are still issued as polygons defining ash boundaries only, the method presented in this paper is likely to be of relevance to volcanic ash forecasters.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to make use of ash polygons based on various sources of information about ash presence (including inputs from skilled forecasters) and demonstrated reliability make this method ideal for operational use. The sources considered in this paper have not been optimized to make quantitative forecasts of mass loadings, which are in increasing demand; this issue is addressed in another paper [ Zidikheri et al , ]. However, while volcanic ash advisories are still issued as polygons defining ash boundaries only, the method presented in this paper is likely to be of relevance to volcanic ash forecasters.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we extend the inverse modeling methodology of Zidikheri and Potts () and Zidikheri et al (, , ) for this purpose. Using this method, the authors demonstrated that various source parameters such as the height, diameter, start time, vertical, temporal, and particle size mass distributions can be inferred and lead to better forecasts.…”
Section: Model Calibration Methodologymentioning
confidence: 99%
“…This is conventionally a uniform line source with the same emission rate specified at all altitudes from the summit up to a maximum height as determined by various ash cloud height estimates (Witham et al, ). For large eruptions with significant umbrella cloud growth, this approach is inappropriate and must be replaced with both a broader source mass distribution in the horizontal and a source mass distribution in the vertical biased toward higher altitudes (Zidikheri et al, , ). However, for the purpose of analyzing ash detections only, once the maximum height has been specified, the vertical mass distribution below the maximum height is irrelevant and a vertically uniform and horizontally broad cylindrical distribution is adequate to represent the umbrella cloud effects.…”
Section: Forecast Verification Methodologymentioning
confidence: 99%
See 2 more Smart Citations